Um olhar sobre o tempo no envelhecimento - Karat, Flora Ricciopo (2019)
This work aims at bringing the reader a new perspective of time, beyond the linear and objective models presented by the experience over the years, restrained to the chronological time. This new outlook aims at understanding time from the point of view of the consciousness of the subjective experiences, in the relationship between the inner and outside world of the Self. By exploring this core of the consciousness level, I intend to investigate how the dialetic of time may interfere objectively and subjectively in the life of the aging individual